Bale Buga Desa Adat Tenganan Pegringsingan - Sebuah Eksplorasi Tektonika Bangunan - Surya Darma, Kadek Agus; Suryada, I Gusti Agung Bagus (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 10 No 1 (2023): April 2023, 2023)
The bale buga of Tenganan Pegringsingan demonstrates simple tectonics. It is, however, fully loaded with exciting and unique traditional knowledge and carpentry skills. This building could be used as a medium for learning in architectural education, especially in the structure and construction of traditional buildings. This research collects data through site observation, architectural documentation, and on-site empirical measurements. This process is also enriched by structured discussions with local respondents, including local undagi (architect) and owners of the bale buga . Data analysis is carried out in stages, embracing phases of data classification, definition, and description of every single structural element of the bale buga before they are ready to be included in learning materials to improve students’ competencies, knowledge, and skills in architectural drawing capacity through the stages of classifying, defining and elaborating the elements of bale buga construction. This information is presented as teaching materials that are comprehensively used to achieve students’ competence, knowledge, and skills in architectural drawing. The result of this study is a tectonics exploration of the bale buga that includes detailed constructions of its floor, wall, and roof; building construction materials in use, dimensions, and scale; and functions of the bale buga in the context of traditional homes in the Tenganan Pegeringsingan Village. Keywords: tectonics; bale buga ; Balinese traditional architecture; Tenganan Pegringsingan Abstrak Bale buga Tenganan Pegringsingan menunjukan tektonika yang sederhana, namun sarat dengan tinggalan pengetahuan serta keterampilan pertukangan tradisional yang menarik dan unik. Bangunan ini dapat dipakai sebagai media pembelajaran di dalam pengembangan dunia pendidikan arsitektur, khususnya untuk bidang struktur konstruksi bangunan tradisional. Proses pendataan di dalam penelitian ini dilaksanakan melalui observasi, pendokumentasian, serta pengukuran langsung secara empiris di lokasi penelitian. Data-data yang diperoleh juga diperkaya oleh hasil diskusi terstruktur dengan para narasumber setempat, seperti para undagi dan pemilik bale buga . Proses analisis dilakukan melalui tahapan pengklasifikasian, pendefinisian dan penjabaran elemen-elemen konstruksi bale buga . Informasi yang disajikan disiapkan agar secara komprehensif bisa dimanfaatkan sebagai bahan ajar untuk mencapai kompetensi, pengetahuan dan keterampilan menggambar mahasiswa di bidang arsitektur. Hasil dari penelitian ini adalah eksplorasi tektonika bale buga yang meliputi penggambaran ilustrasi sistem konstruksi sambungan mulai dari elemen lantai, dinding dan atap; jenis bahan penyusun konstruksi; dimensi eksisting bale buga ; serta penjelasan terkait fungsi bale buga dalam konteks rumah tradisional di Desa Tenganan Pegeringsingan. Kata kunci: tektonika; bale buga ; arsitektur tradisional Bali; Tenganan Pengringsingan